Geschichte der venezianischen Malerei, Band 1 Band 1: Von den Mosaiken in San Marco bis zum 15. Jahrhundert - Brucher, Günter
The present manuscript is meant as volume I of a series of books comprising four volumes in total. Except for Hüttinger´s barely sufficient survey, its object, an overall presentation of Venetian painting from the early beginnings till the 18th and 19th centuries, has almost been neglected by German scholars up to this day. The same may be said about Italian investigations, the more so as the book-series Pittura nell Veneto (edited in several volumes) strongly resembles a corpus opus: It does comprise the most important facts (e.g.the biographies of the artists) and provides a fine collection of pictures as well as a presentation of the momentary status of research, making every effort to completeness, but purely artistic, developmental, iconographic, style-genetic and coloring problems are examined in a rather rudimentary manner and, moreover, organised in a way which cannot easily be followed by the reader. When overlooking the numerous single publications by Italian authors, one will realize that they share an almost incomprehensible timidity of analysing the paintings thoroughly. Such an attempt, however, must be considered the only proper way to get to the root of both development and peculiarity of Venetian painting, so well characterized by Hetzer´s term "ornamental".Comparative work interpretations will have to meet this scientific deficiency. Proceeding from a descriptive technique based on the specific structure and thustaking form as well as colour into consideration, the theories of morphology and perceptive psychology largely contribute to this intention. Only on the ground of visual findings which have been proven analytically, questions of how to date properly, of how to decide possible work participation and/or dependence of the artists can be clarified, with the additional goal of reaching hermeneutic results and working out what is considered typically Venetian.- Volume I starts out with a survey of Venetian history till the middle of the 15th century, leading from the mosaics of San Marco (beginning with the 11th century) to the second half of the quattrocento. Contrary to usual scholarly views, the art of mosaics is classed with the art of painting, for it incorporates the very same criteria of painting as to form, style and arrangement. The main point here is to bring O.Demus´s scientific results with reference to chronology, genesis of style etc. in accordance with those of Italian scientists who quite frequently hold different views, and to come up with personal decisions at times. Prevailing in the mosaics of San Marco, Byzantinism conditions Venetian painting (fresco and table painting, which gets into being at the end of the 13th century) and remains dominant till late into the trecento. Here it is first observed with Paolo Veneziano, who seldom glances at the development of the occidental style on Terraferma (e.g. Giotto). The ensuing breakthrough of the Gothic style is found with Lorenzo Veneziano. In its course, Byzantine, Upper-Italian and transalpine stimulations fuse into a remarkable symbiosis. Hence investigations in the field of coloring, which have rarely been dealt with in specialized literature, play and hitherto will play a decisive rôle in the evaluation of Venetian painting. A special chapter is dedicated to N. Semitecolo who stands under Padua´s influence (cf. Guariento). After recurrences to conservative Byzantine elements in the last third of the trecento, the international Gothic style celebrates its entry into Venetian painting (cf Jacobello de Fiore) under the strong influence of Gentile da Fabriano. At the same time, first signs of a more modern attitude to painting can be observed with Giambono. Far longer than in the rest of Italy, painting in Venice was partial to the tendencies of the international Gothic as well as to elements of splendour, decoration and space. This explains why first indications of the early renaissance appear rather late, mainly in the works of G. d´Al